Impact of digitalization on tax revenue collection in Algeria: An empirical study for the period 2014–2024 - Siham, Taleb Hacine (The International tax journal, 2025)
This study aims to measure the impact of digitalization on tax revenue collection in Algeria over the period 2014–2024. In the theoretical part of the study, we addressed the fundamental concepts related to the study variables, expressed as digitalization and tax revenue collection. An empirical investigation was then conducted using the Autoregressive Distributed Lag (ARDL) model, due to its ability to examine dynamic relationships between variables in both the short and long run. Tax revenue collection was considered the dependent variable, while digitalization served as the independent variable through: the number of automated machines, the information and communication technology (ICT) usage index, and the number of hours required for tax payment. Additionally, economic growth, total public tax revenues, and petroleum tax revenues were included as control variables. The study revealed several key findings, most notably the existence of a positive and significant relationship between digitalization and tax revenue collection in both the short and long run, except for the tax payment hours indicator in the long run. This confirms that advancements in technological infrastructure contribute to improving the efficiency of the tax system, reducing compliance gaps, and decreasing the hours required for tax payment.